Antimicrobial resistance genes harbored in invasive Acinetobacter calcoaceticus-baumannii complex isolated from Korean children during the pre-COVID-19 pandemic periods, 2015–2020 - Kang, Hyun Mi; Kim, Kyung Ran; Kim, Gahee; Lee, Dong-gun; Kim, Yae Jean; Choi, Eun Hwa; Lee, Jina; Yun, Ki Wook (Frontiers in Cellular and Infection Microbiology, 2024)
Background Acinetobacter baumannii (AB) has emerged as one of the most challenging pathogens worldwide, causing invasive infections in the critically ill patients due to their ability to rapidly acquire resistance to antibiotics. This study aimed to analyze antibiotic resistance genes harbored in AB and non-baumannii Acinetobacter calcoaceticus-baumannii (NB-ACB) complex causing invasive diseases in Korean children. Methods ACB complexes isolated from sterile body fluid of children in three referral hospitals were prospectively collected. Colistin susceptibility was additionally tested via broth microdilution. Whole genome sequencing was performed and antibiotic resistance genes were analyzed. Results During January 2015 to December 2020, a total of 67 ACB complexes were isolated from sterile body fluid of children in three referral hospitals. The median age of the patients was 0.6 (interquartile range, 0.1–7.2) years old. Among all the isolates, 73.1% (n=49) were confirmed as AB and others as NB-ACB complex by whole genome sequencing. Among the AB isolates, only 22.4% susceptible to carbapenem. In particular, all clonal complex (CC) 92 AB (n=33) showed multi-drug resistance, whereas 31.3% in non-CC92 AB (n=16) (P<0.001). NB-ACB showed 100% susceptibility to all classes of antibiotics except 3rd generation cephalosporin (72.2%). The main mechanism of carbapenem resistance in AB was the blaoxa23 gene with ISAba1 insertion sequence upstream. Presence of pmr gene and/or mutation of lpxA/C gene were not correlated with the phenotype of colistin resistance of ACB. All AB and NB-ACB isolates carried the abe and ade multidrug efflux pumps. Conclusions In conclusion, monitoring and research for resistome in ACB complex is needed to identify and manage drug-resistant AB, particularly CC92 AB carrying the blaoxa23 gene.